Facets of autobiographical memory in adolescents with major depressive disorder and never-depressed controls - Kuyken, W; Howell, R (2006)
Adolescence is a crucial developmental window because it involves elaboration of the self-concept, the laying down of lifelong autobiographical memories, and the development of emotional resilience during a time of substantial risk for mood problems. Autobiographical memory retrieval plays an important role in depression both in adults (van Vreeswijk and de Wilde, 2004) and adolescents (Kuyken, Howell, and Dalgleish, 2005; Park, Goodyer, and Teasdale, 2002). This study examined facets of autobiographical memory associated with memory retrieval in never-depressed and currently depressed adolescents: Personal importance, imagery, recency, source monitoring, and field-observer perspective. Compared with never-depressed adolescents, adolescents with depression were significantly more likely to retrieve memories from an observer perspective and more recent time period, preferentially rehearsed negative memories and rated their memories as more personally important. Depressed adolescents who reported a history of trauma retrieved more vivid autobiographical memories than depressed adolescents not reporting such a history, had rehearsed them more frequently, and reported more confidence in their veracity. © 2006 Psychology Press Ltd.